Minimum Wages and the Labor Market Effects of Immigration - Anthony Edo; Hillel Rapoport (Center for Economic Studies and ifo Institute (CESifo), 2017)
We exploit the non-linearity in the level of minimum wages across US States created by the coexistence of federal and state regulations to investigate how minimum wages affect the labor market impact of immigration. We find that the effects of immigration on labor market outcomes of native workers within a given state-skill cell are more negative in U.S. States with low minimum wages (i.e., where the federal minimum wage is binding). The results are robust to instrumenting immigration as well as state minimum wages, and to implementing a difference-in-differences strategy comparing U.S. States where effective minimum wages are fully determined by federal standards over the whole period considered (2000-2013) to U.S. States where this is never the case. Our results therefore underline the important role played by minimum wages in mitigating any adverse labor market effects of immigration.
Keywords: F22; J61; 330; immigration; minimum wage; labor market